2023
DOI: 10.3389/fvets.2023.1022838
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of fimA genotype of Porphyromonas gulae with the severity of periodontal disease and the number of permanent teeth in dogs

Abstract: Previous research has demonstrated that Porphyromonas gulae (P. gulae) significantly contributes to the development of periodontal disease in dogs. Porphyromonas gulae is divided into three subtypes according to the 41-kDa filamentous appendage (fimA), defined as types A, B, and C. This study aimed to elucidate the association between fimA type of P. gulae with the number of permanent teeth, reflecting the severity of periodontal disease. Two hundred twenty-five dogs were categorized by P. gulae fimA type as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Without considering the number of FimA genotypes detected in the oral cavity, dogs with FimA genotypes A, B, or C of P. gulae have a significantly higher periodontal severity score than dogs with P. gulae -negative, which was consistent with a previous study 10 . In the present study, we also analyzed the number of FimA genotypes, and we found that all dogs with 1 to 3 FimA genotypes have significantly higher periodontal severity scores than the dogs negative for P. gulae .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Without considering the number of FimA genotypes detected in the oral cavity, dogs with FimA genotypes A, B, or C of P. gulae have a significantly higher periodontal severity score than dogs with P. gulae -negative, which was consistent with a previous study 10 . In the present study, we also analyzed the number of FimA genotypes, and we found that all dogs with 1 to 3 FimA genotypes have significantly higher periodontal severity scores than the dogs negative for P. gulae .…”
Section: Discussionsupporting
confidence: 91%
“…Dysbiosis of the human oral microbiome is detrimental to health, leading to periodontal disease. A recent study of 225 mostly small dogs revealed that, within the first 50 months of life, the severity of periodontal disease varied according to the genotype of P. gulae FimA in the oral cavity 10 . This study categorized dogs into only three types of FimA genotypes: A, B, and C; however, the actual FimA genotype distribution in the oral cavity of dogs is classified into seven types (A, B, C, A/B, A/C, B/C, A/B/C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation